2015
DOI: 10.4103/0975-1475.172445
|View full text |Cite
|
Sign up to set email alerts
|

Dental age estimation of growing children by measurement of open apices: A Malaysian formula

Abstract: Background:Age estimation is of prime importance in forensic science and clinical dentistry. Age estimation based on teeth development is one reliable approach. Many radiographic methods are proposed on the Western population for estimating dental age, and a similar assessment was found to be inadequate in Malaysian population. Hence, this study aims at formulating a regression model for dental age estimation in Malaysian children population using Cameriere's method.Materials and Methods:Orthopantomographs of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…However, due to geographic differences between different regions from India, they proposed another formula, namely Age = 9.402 − 0.879C (C = 0 for the center and north of India and 1 for the south) + 0.663N 0 − 0.711s − 0.106sN 0 , which explained 89.7% of the total variance [ 12 ]. Cugati et al developed a specific formula for Malaysian populations, namely, Age = 11.368 − 0.345g + 0.553N 0 − 1.096s − 0.380sN 0 , which yielded an R 2 value of 0.871 [ 18 ]. Cameriere developed two main formulas to assess dental age based on open apices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, due to geographic differences between different regions from India, they proposed another formula, namely Age = 9.402 − 0.879C (C = 0 for the center and north of India and 1 for the south) + 0.663N 0 − 0.711s − 0.106sN 0 , which explained 89.7% of the total variance [ 12 ]. Cugati et al developed a specific formula for Malaysian populations, namely, Age = 11.368 − 0.345g + 0.553N 0 − 1.096s − 0.380sN 0 , which yielded an R 2 value of 0.871 [ 18 ]. Cameriere developed two main formulas to assess dental age based on open apices.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Angelakopoulos et al developed a new formula—based on the Cameriere approach—using Bayesian methods, in South African children [ 16 ]. Additionally, numerous authors have shown this method to be more accurate in estimating age compared to others such as Demirjian, Nolla, Haavikko, or Willems [ 17 , 18 ]. However, the mean difference between chronological and dental age, as estimated by this method, has been shown to be variable in different studies, with some of them having been performed on similar populations [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To create a regression model, similar to the study by Cugati et al (17), gender and morphological variables such as the standardized sum of values of teeth with open apices, the number of teeth with closed apices, and their interactions were used. In some studies, other variables such as standardized values of teeth number 1 to 7 were also included in the model (2,3,12,(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…This method was evaluated on a large number of children from multiple European countries, including Croatia, Germany, Kosovo, Italy, Slovenia, Spain, and the United Kingdom, yielding a common formula effective for all these countries [28]. The validity and accuracy of Cameriere's method were tested on several sample groups from various nationalities [29][30][31][32][33], revealing that the original regression model developed by Cameriere may not always be applicable to other countries because tooth development differed among populations and varied across ethnic groups and geographic areas [34]. Moreover, diet, socioeconomic status, nutritional habits, and lifestyle all have an impact on tooth development [19].…”
Section: Introductionmentioning
confidence: 99%